Influences on the decision to use an osteoarthritis diagnosis in primary care: a cohort study with linked survey and electronic health record data. Issue 5 (May 2016) - Jordan, K.P.; Tan, V.; Edwards, J.J.; Chen, Y.; Englund, M.; Hubertsson, J.; Jöud, A.; Porcheret, M.; Turkiewicz, A.; Peat, G.
Summary: Objective: Clinicians may record patients presenting with osteoarthritis (OA) symptoms with joint pain rather than an OA diagnosis. This may have implications for OA research studies and patient care. The objective was to assess whether older adults recorded with joint pain are similar to those with a recorded OA diagnosis. Method: A study of adults aged ≥50 years in eight United Kingdom general practices, with electronic health records linked to survey data. Patients with a recorded regional OA diagnosis were compared to those with a recorded joint pain symptom on socio-demographics, risk factors, body region, pain severity, prescribed analgesia, and potential differential diagnoses. A sub-group was compared on radiographic knee OA. Results: Thirteen thousand eight hundred and thirty-one survey responders consented to record review. One thousand four hundred and twenty-seven (10%) received an OA ( n = 616) or joint pain ( n = 811) code with wide practice variation. Receiving an OA diagnosis was associated with age (75+ compared to 50–64 OR 3.25; 95% Credible intervals (CrI) 2.36, 4.53), obesity (1.72; 1.22, 2.33), and pain interference (1.45; 1.09, 1.92). Analgesia management was similar. Radiographic OA was common in both groups. A quarter of those with a joint pain record received an OA diagnosis in the following 6 years. Conclusion: Recording OA diagnoses are less common than recording a joint pain symptom and associated with risk factors and severity. OA studies in primary care need to consider joint pain symptoms to understand the burden and quality of care across the spectrum of OA. Patients recorded with joint pain may represent early cases of OA with need for early intervention.